WP15 ConCorD state-of-the-art report (container corrosion under disposal conditions) - Muñoz, Andrés G.; Abdelouas, Abdesselam; Alonso, Ursula; Fernández, Ana María; Bernier-Latmani, Rizlan; Cherkouk, Andrea; Gaggiano, Roberto; Hesketh, James; Smart, Nick; Padovani, Cristiano; Mijnendonckx, Kristel; Montoya, Vanessa; et al. (Frontiers in Nuclear Engineering, 2024)
A sealed container for the geological disposal of spent nuclear fuel and vitrified high-level waste is the only component of a deep geological repository that provides complete containment of radionuclides. As such, attention is focused on its lifetime. The lifetime of the container is influenced by material degradation processes during disposal and is typically of the order of several millennia and, for some container materials, up to one million years. Designing, manufacturing, and predicting the performance of containers over such long periods requires an in-depth understanding of their material properties, fabrication processes, and degradation mechanisms. Scientific and technological progress can improve both the performance of containers and the robustness of lifetime predictions. Optimization of these aspects is of primary importance for many national radioactive waste disposal programs. In this article, the state of the art of complex coupled degradation processes, as well as the optimization potential of novel container materials, is presented. Furthermore, the existing tools allowing the prediction of long-term barrier integrity are discussed.